EKSISTENSI MASYARAKAT ISLAM DI CINA; LAOBAN LANZHO LAMIAN - Teuku Zulyadi (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2019)
The religions in China have active communication with foreign religious bodies and personnel to contribute to world peace and strong friendships between the Chinese people and from other countries. Ten classic Islamic books, including the Koran, have been translated into Chinese and Uygur and published under the direction of the Chinese Islamic Association. These books are spread throughout China. This article narrates the daily life of the Islamic community in China. The data is based on the author's observations while living in China in taking doctoral studies and in-depth interviews with the community and the mosque's imam. The Islamic community in China is experiencing rapid growth, both in terms of numbers, economy and other activities. Their existence is very easy to know, halal restaurants are very affordable and spread in many places. There are special markers to make sure it is a halal restaurant, such as the distinctive ornaments of Islam that are green, calligraphy verses of the Koran, pictures of mosques, Muslim-clad sellers. Among all, the most important is halal writing in Arabic. Generally, Muslim traders sell lanzho lamian, a noodle typical from the lanzho area which is a Muslim majority area. This food is very famous not only for Muslims. The Chinese themselves also really like it, because the manufacturing process is guaranteed to be healthy. The process of making noodles is done in front of the buyer, such as stirring flour, grinding to become noodles done by hand, without any tools. Keywords: China, religion, Islam, society, lanzho lamian